KONTRIBUSI SEKTOR INDUSTRI PENGOLAHAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) 2015-2019 KABUPATEN BONE BOLANGO - Imbran, Harijono; Machmud, Joice; Lebie, Lily (Akademika, 2023)
This study aims to analyze the contribution of the manufacturing sector to the Gross Regional Domestic Product of Bone Bolango Regency. This study uses a quantitative analysis approach with a five-year time series database of Gross Regional Domestic Product (2015-2019). The results of the study found that the processing industry was able to contribute to the Gross Regional Domestic Product of Bone Bolango Regency in the last five years (2015-21019). The amount of contribution can be seen from the model summary table which has a RSequare value or an average contribution of 96.4 percent. This means that the manufacturing sector is able to contribute an average of 96.4 percent. The regression equation formed is: Y = 506,674 + 13,327X, illustrating that if there is no contribution from the manufacturing sector, the Gross Regional Domestic Product of Bone Bolango Regency will only have an average value of Rp. 506,674 billion. While the regression coefficient with a value of 13.327 shows that every time there is an increase in one unit value (X = Processing Industry) the value of Y (Gross Regional Domestic Product) will increase by one unit as well and vice versa